1997
DOI: 10.1095/biolreprod57.6.1502
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Possible Novel Role of Phospholipid Hydroperoxide Glutathione Peroxidase in Rat Epididymal Spermatozoa1

Abstract: The selenoenzyme phospholipid hydroperoxide glutathione peroxidase (PHGPx, EC 1.11.1.12) is present, in both free and membrane-bound form, in several mammalian tissues. It utilizes thiols such as glutathione to specifically scavenge phospholipid hydroperoxides. The testis exhibits the highest PHGPx-specific activity so far measured, and interest in the presence and function of the enzyme in this tissue has recently grown. Here we report the localization of PHGPx in rat epididymal spermatozoa and its distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(73 citation statements)
references
References 37 publications
3
66
0
4
Order By: Relevance
“…PHGPx is a selenoperoxidase that plays a crucial role in spermatogenesis both in the testis and in the epididymis (22).…”
Section: Resultsmentioning
confidence: 99%
“…PHGPx is a selenoperoxidase that plays a crucial role in spermatogenesis both in the testis and in the epididymis (22).…”
Section: Resultsmentioning
confidence: 99%
“…The characterization of NOX5 and its putative role in ROS production are important to understand the relationship between the redox state and the biological function of sperm. A growing body of evidence indicates a role for ROS in a variety of sperm functions, including capacitation (Leclerc et al 1997), tyrosine phosphorylation (Aitken et al 1996, Leclerc et al 1997, Baumber et al 2003, O'Flaherty et al 2006, chromatin condensation (Godeas et al 1997), regulation of intracellular pH ) and acrosomal exocytosis (Rivlin et al 2004). Several studies including ours (Aitken & Clarkson 1987, Aitken et al 1995, Tselkas et al 2000, O'Flaherty et al 2003, Sabeur & Ball 2006 have shown that mammalian spermatozoa are capable of generating ROS but the biochemical mechanisms by which ROS are generated in mammalian spermatozoa are not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…The appearance of nPHGPx in late spermiogenesis (24,26,28) coincides with DNA condensation. The ability of PHGPx to act on -SH groups of protamine as alternate substrates (24,39) prompted the idea that its nuclear variant is indispensable for chromatin condensation by cross-linking protamine thiols. This process is also considered to guarantee appropriate sperm function and arrest of proliferation, once the germ line cells have reached their final state of differentiation (24,26).…”
Section: Discussionmentioning
confidence: 99%
“…Rather a unique role of PHGPx in cellular differentiation would be compatible with the outcome of the reverse genetics approach. The use of protamine -SH groups as an alternate substrate of PHGPx, as demonstrated for testis (39,24), might be taken as a model for a more general principle of how the enzyme might regulate cell division, and the nuclear form would surely be predestined to fulfill such demands.…”
Section: Discussionmentioning
confidence: 99%